Insider dealing and market manipulation - Crha, Jiří; Hnilica, Jiří, 1976-; Horník, Tomáš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
The issue of capital market protection, especially from manipulation with financial instruments' prices and abuse of inside information, forms the content of this diploma thesis. After the legal introduction of market manipulation in EU directives and regulations, which gives manipulation relevant context, there follows the analysis of particular forms of manipulation, which can be used to influence prices of investment instruments. Then, analysis of impact of investment recommendation to selected stock prices (i.e. NWR, ERSTE and Telefónica O2), which are traded on Czech stock market RM-System, is performed. Final chapter of the thesis handles the analysis of some market manipulation and insider trading cases from the past, together with the discussion of impacts of stricter regulation of financial markets to their efficient functioning.
Vedoucí práce: Jiří Hnilica
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: international Management [obor dipl. práce]; diplomové práce; master's theses